Application of Weighted Product (WP) Method in Selection of Superior Seed Varieties of Sugar Cane - Alanis Humairoh; Yani Maulita; Nurhayati (Journal of Computer Science and Informatics Engineering, 2022)
Sugarcane (Saccharum officinarum Linn) is a raw material for sugar production. PT. Perkebunan Nusantara II is one of the nurseries and sugarcane processing places in North Sumatra. The results of observations on sugarcane production are always increasing but the results are not too optimal. Determination of superior varieties of sugarcane seeds is very appropriate to be one of the factors supporting the development of sugarcane production so that there is no longer sugarcane milling period and low yields which can lead to less than optimal sugar production. To overcome this, it is necessary to build a system that can help determine superior seed varieties in sugarcane. The Weighted Product (WP) method in a decision support system is a method of completion by using multiplication to link the attribute rating, where the attribute rating must be raised first with the weight of the attribute in question. This decision support system with the WP method was created to assist in the selection of high-yielding sugarcane varieties.